Filial responsibilities and psychological wellbeing among Chinese adolescents in poor single-mother families: does parental warmth matter? - Leung, Janet T. Y.; Shek, Daniel T. L. (Frontiers in Psychology, 2024)
Adolescent children raised in single-mother households, particularly those living in poverty, often need to assume more instrumental and emotional familial responsibilities to cope with family challenges. This study examined the relationships between these filial responsibilities and adolescent psychological wellbeing, as well as the moderating effect of maternal warmth on these relationships. The sample comprised 325 Chinese adolescent children (43.3% girls; Mage = 13.5) from economically disadvantaged single-mother families in Hong Kong. The results indicated that adolescents' instrumental filial responsibilities were positively associated with their life satisfaction. Emotional filial responsibilities, on the other hand, were positively linked to life satisfaction and negatively associated with depression. Furthermore, maternal warmth was found to moderate the relationship between emotional filial responsibilities and life satisfaction. Adolescents who perceived higher levels of maternal warmth and performed more emotional filial responsibilities reported greater life satisfaction than those who performed fewer such responsibilities. Furthermore, the moderating effect of maternal warmth on the relationship between instrumental filial responsibilities and life satisfaction varied between boys and girls. Additionally, the age of the adolescent moderated the effect of maternal warmth on the relationship between emotional filial responsibilities and adolescent anxiety. These findings suggest that filial responsibilities do not necessarily impede adolescent wellbeing. Instead, maternal warmth appears to be a crucial family factor that influences the nature of the relationship between filial responsibilities and adolescent wellbeing. These insights are valuable for family scholars and practitioners, informing the design of supportive services to enhance the psychological wellbeing of Chinese adolescents from economically disadvantaged single-mother families.